Global 3-D distribution of aerosol composition by synergistic use of CALIOP and MODIS observations - R. Kudo; A. Higurashi; E. Oikawa; M. Fujikawa; H. Ishimoto; T. Nishizawa (Atmospheric Measurement Techniques, 2023)
For the observation of the global three-dimensional distribution of aerosol composition and the evaluation of the shortwave direct radiative effect (SDRE) by aerosols, we developed a retrieval algorithm that uses observation data from the Cloud–Aerosol Lidar with Orthogonal Polarization (CALIOP) on board the Cloud–Aerosol Lidar Infrared Pathfinder Satellite Observations (CALIPSO) satellite and the Moderate Resolution Imaging Spectroradiometer (MODIS) on board Aqua. The CALIOP–MODIS retrieval optimizes the aerosol composition to both the CALIOP and MODIS observations in the daytime. Aerosols were assumed to be composed of four aerosol components: water-soluble (WS), light-absorbing (LA), dust (DS), and sea salt (SS) particles. The outputs of the CALIOP–MODIS retrieval are the vertical profiles of the extinction coefficient (αa), single-scattering albedo (ω0), asymmetry factor (g) of total aerosols (WS+LA+DS+SS), and αa of WS, LA, DS, and SS. Daytime observations of CALIOP and MODIS in 2010 were analyzed by the CALIOP–MODIS retrieval. The global means of the aerosol optical depth (τa) at 532 nm were 0.147±0.148 for total aerosols, 0.072±0.085 for WS, 0.027±0.035 for LA, 0.025±0.054 for DS, and 0.023±0.020 for SS. τa of the CALIOP–MODIS retrieval was between those of the CALIPSO and MODIS standard products and was close to the MODIS standard product. The global means of ω0 and g were 0.940±0.038 and 0.718±0.037; these values are in the range of those reported by previous studies. The horizontal distribution of each aerosol component was reasonable; for example, DS was large in desert regions, and LA was large in the major regions of biomass burning and anthropogenic aerosol emissions. The values of τa, ω0, g, and fine and coarse median radii of the CALIOP–MODIS retrieval were compared with those of the AERONET products. τa at 532 and 1064 nm of the CALIOP–MODIS retrieval agreed well with the AERONET products. The ω0, g, and fine and coarse median radii of the CALIOP–MODIS retrieval were not far from those of the AERONET products, but the variations were large, and the coefficients of determination for linear regression between them were small. In the retrieval results for 2010, the clear-sky SDRE values for total aerosols at the top and bottom of the atmosphere were -4.99±3.42<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="e400f353e553e3d00dfc8e8beb553623"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-16-3835-2023-ie00001.svg" width="64pt" height="10pt" src="amt-16-3835-2023-ie00001.png"/></svg:svg> and -13.10±9.93<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="70pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="3afa36f3598cd775cd5cd24385673b4f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-16-3835-2023-ie00002.svg" width="70pt" height="10pt" src="amt-16-3835-2023-ie00002.png"/></svg:svg> W m−2, respectively, and the impact of total aerosols on the heating rate was from 0.0 to 0.5 K d−1. These results are generally similar to those of previous studies, but the SDRE at the bottom of the atmosphere is larger than that reported previously. Consequently, comparison with previous studies showed that the CALIOP–MODIS retrieval results were reasonable with respect to aerosol composition, optical properties, and the SDRE.